Implementation of computerized maintenance management systems (CMMS) in the government building at Putrajaya / Siti Ruqaiyah Shariff - Shariff, Siti Ruqaiyah (2014)
In the government buildings at Putrajaya, the maintenance management is emphasizing the use of Computerized Maintenance Management Systems (CMMS) for conducting the maintenance activities. Putrajaya Public Works Department is in charged and responsible for the maintenance contractor to implement the use of CMMS in the government building. For that matter, this research has discussed on the implementation of CMMS in the government building at Putrajaya.